Insecticide imidacloprid induces morphological and DNA damage through oxidative toxicity on the reproductive organs of developing male rats - Bal, R; Naziroğlu, M; Türk, G; Yılmaz, Ö; Kuloğlu, T; Etem, E; Baydaş, G (My University, 2012)
We investigated whether treatment with imidacloprid would induce morphological changes, DNA fragmentation, antioxidant imbalance and apoptosis in the reproductive system of developing male rats. Twenty-four male rats were included in this 90-day study, starting at 7 days of age. The rats were divided into four groups. The first group was used as control. The second, third and fourth groups received oral 0.5-, 2- and 8-mg/kg imidacloprid, respectively. Serum, spermand testis sampleswere collected fromall groups at the end of the experimental period. Theweights of the epididymis, vesicula seminalis, epididymal sperm concentration, body weight gain, testosterone and reduced glutathione values were lower in the imidacloprid-treated groups than that in the controls. All treated groups had increased lipid peroxidation, fatty acid concentrations and higher rates of abnormal sperm. Apoptosis and fragmentation of seminal DNA were higher in rats treated at the two higher doses of imidacloprid. These results show that this compound has a negative effect on sperm and testis of rats
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: imidacloprid oxidative stress apoptosis testis fatty acids